Mechanistic insights into modified Danggui Buxue Decoction for diabetic retinopathy via integrative analysis - Poon, Lee Yam; Hsu, Li Mei; Lam, Lai Kwan; Huang, Xiaoqing; Xu, Pengli; Liang, Qiuer; Xie, Pengcheng; Yang, Shuyu (Frontiers in Endocrinology, 2025)
ObjectiveThis study explores the therapeutic potential and mechanisms of Modified Danggui Buxue Decoction (MDBD) in diabetic retinopathy (DR) using network pharmacology, bioinformatics, machine learning, Mendelian randomization (MR), molecular docking, and in vitro experiments.MethodsA network pharmacology was constructed in order to screen core components and targets. Analysis of samples from the GEO database was performed for target and immune cell analysis, resulting in the identification of significantly differentially expressed core genes (SDECGs). A machine learning model was utilized to screen feature genes and construct nomogram. Preliminary validation was carried out using molecular docking, another GEO dataset, and MR. Subsequently, samples were clustered based on SDECGs expression and consensus clustering, followed by an analysis between clusters. SDECGs expression was scored and differences between clusters were analyzed. Finally, in vitro experiments were conducted on MMCs to assess the effects of beta-sitosterol, the primary active component of MDBD, and siRNA on DR-related biomarkers using CCK-8 assays, ELISA, western blotting and RT-qPCR.ResultsThis study identified the core components of MDBD, including quercetin, stigmasterol, beta-sitosterol, kaempferol, and 14 differentially expressed SDECGs between DR and control groups, with both positive and negative immune cell regulatory effects. Five feature genes (CCND1, ERBB2, INSR, TP53, SERPINE1) were identified and used to construct a predictive model. MR analysis revealed a causal link between elevated ERBB2 levels and increased DR risk (Odds Ratio [OR]=1.860, 95% CI: 1.247-2.774, P = 0.002) using the weighted median method. Beta-sitosterol displayed high binding affinity with CCND1, ERBB2, INSR, and SERPINE1. Cluster analysis categorized DR samples into four groups, with C1 showing low and C2 high SDECG expression and immune cell upregulation. Significant differences in SDECGs and DEGs scores were observed between C1 and C2. In vitro, ERBB2 expression was significantly elevated in DR cell model. Beta-sitosterol inhibited ERBB2 protein and mRNA expression and reduced IL-1β, VEGF, and ANGPTL6 secretion. ERBB2 inhibition also reduced these biomarkers.ConclusionMDBD treats DR by targeting SDECGs, modulating immune responses, and reducing inflammation. Beta-sitosterol and ERBB2 inhibition showed significant therapeutic effects, offering valuable insights for clinical application and future research directions.